The persistence of equity: lessons from the trust - McFarlane, B (Hart Publishing, 2023)
This chapter aims to use the example of the trust to address the question that motivates this book: 150 years after the Judicature Act 1873, is there any reason (other than simple curiosity as to the historical origin of a particular rule or principle) to continue to distinguish between common law and equity? As well as examining the trust, and equity more generally, it considers a still broader question: does the role of equity today reveal anything of wider significance about the nature of English law, and therefore of the common law as applied in jurisdictions around the world? Certainly, the continued presence, and prominence, of a body of rules and principles referred to as ‘equity’ is one of the more striking features of English law....